2020
DOI: 10.1371/journal.pone.0242044
|View full text |Cite
|
Sign up to set email alerts
|

Race, explicit racial attitudes, implicit racial attitudes, and COVID-19 cases and deaths: An analysis of counties in the United States

Abstract: Objectives To examine the potential moderating effects of explicit racial attitudes and implicit racial attitudes on the relationship between percent of Black county residents and COVID-19 cases and deaths. Methods We collected data from a variety of publicly available sources for 817 counties in the US. (26% of all counties). Cumulative COVID-19 deaths and cases from January 22 to August 31, 2020 were the dependent variables; explicit racial attitudes and implicit racial attitudes served as the moderators; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
0
24
1
Order By: Relevance
“…Health behaviors and outcomes are a function of factors at multiple levels, including intrapersonal and interpersonal processes, institutional factors, community factors, and societal laws and statutes 9 . With respect to COVID-19, most of the scholarship has focused on intrapersonal factors 1 , 2 , 3 , 4 , 5 , but there is evidence that community and public policy factors can and do influence the incidence of COVID-19 cases and deaths 11 , 12 , 13 , 45 . Nevertheless, scholars have yet to examine the association of PA with COVID-19 cases and deaths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health behaviors and outcomes are a function of factors at multiple levels, including intrapersonal and interpersonal processes, institutional factors, community factors, and societal laws and statutes 9 . With respect to COVID-19, most of the scholarship has focused on intrapersonal factors 1 , 2 , 3 , 4 , 5 , but there is evidence that community and public policy factors can and do influence the incidence of COVID-19 cases and deaths 11 , 12 , 13 , 45 . Nevertheless, scholars have yet to examine the association of PA with COVID-19 cases and deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, economic instability is a health risk factor 35 , so the percentage of unemployed county residents ( Unemployed ) and the natural log of the median household Income served as controls. Finally, a host of personal demographics are related to health outcomes and COVID-19 risk and mortality 12 , 36 , 37 . Thus, the percentage of residents who were female ( Female Residents ), White ( White Residents ), and age 65 or older ( 65 or Older ), as well as the rural designation of the county ( Rural ) all served as controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With national age-adjusted death rates revealing an even more profound racial disparity in COVID-19 mortality, it is even more crucial to determine the reasons for these disparities. Although many papers have suggested that structural racism is a critical factor in explaining racial disparities in COVID-19 mortality, we are aware of only six that have demonstrated this relationship empirically by explicitly measuring structural racism [42][43][44][45][46][47]. Tan et al [42] examined the relationship between four measures of structural racism (residential segregation and differences in incarceration rates, economic status, and employment status) and county-level COVID-19 death rates, finding that the degree of residential segregation was significantly related to higher overall death rates.…”
Section: Introductionmentioning
confidence: 99%
“…24 These studies make estimates for each state or country individually and do not allow a relationship between all-cause mortality and Covid-19 mortality to be identified through analysis across smaller area units such as counties. While prior research has documented significant racial and socioeconomic inequities in directly assigned Covid-19 deaths, 2530 few studies have documented how excess mortality in 2020 has differed across sociodemographic or health factors. 31…”
Section: Introductionmentioning
confidence: 99%